2021
DOI: 10.1007/s11356-021-14906-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the bacterioplankton community and the influencing factors in the upper reaches of the Han River basin

Abstract: The upper reaches of the Han River are the source region of water for the Middle Route of China's South-to-North Water Diversion Project, mainly for household, industrial, and irrigation purposes. Planktonic bacteria are more sensitive than macroorganisms to water physical and chemical properties and play a critical role in biogeochemical processes in river ecosystems. In November 2017 and April 2018, a systematic and methodical survey was carried out to evaluate the water quality and bacterial communities, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The above results indicate that N and P nutrients are the main factors driving the communities and function of bacterioplankton in the DJR. Similar to other lakes and reservoirs, T, pH, COD, COD Mn , Cond, and Chla are also important factors affecting the composition of the bacterioplankton communities in the DJR ( Liu et al, 2015 ; Chen Z. J. et al, 2020 ; Dong et al, 2020 ; Qian-Qian et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The above results indicate that N and P nutrients are the main factors driving the communities and function of bacterioplankton in the DJR. Similar to other lakes and reservoirs, T, pH, COD, COD Mn , Cond, and Chla are also important factors affecting the composition of the bacterioplankton communities in the DJR ( Liu et al, 2015 ; Chen Z. J. et al, 2020 ; Dong et al, 2020 ; Qian-Qian et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…The results indicated that Actinobacteria, Bacteroidetes, and Cyanobacteria were the dominant populations. Sun et al (2021) analyzed Han River bacterioplankton upstream of the DJR. The results showed that the dominant genera were Flavobacterium , Planktophila , and Siphonobacter .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterioplankton play a significant role in various geochemical cycles and in the transport of carbon to the microbial food web occurring in aquatic ecosystems such as rivers, water channels, reservoirs, and lakes [ 29 , 30 ]. Bacterioplankton communities’ compositions can serve as indicators of aquatic environmental conditions since they are typically responsive to environmental instabilities and water quality [ 15 , 19 , 31 , 32 , 33 ]. Studies revealed that the bacterioplankton communities’ compositions can be influenced in response to spatiotemporal and environmental changes [ 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Acinetobacter, Exiguobacterium, and Planomicrobium were the dominant genera in WH and WD samples, while unclassified and other genera were abundant in DH and DD samples. In previous studies, these dominant phyla and genera have also displayed significant seasonal and spatial differences in various aquatic environments and their potential association with the water quality [ 28 , 30 , 32 , 40 ]. Furthermore, studies have also reported good water quality during the dry season as compared with the wet season [ 1 , 3 , 41 ].…”
Section: Discussionmentioning
confidence: 99%